2021
DOI: 10.1155/2021/6504648
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Genetic Relationship of Predominant Escherichia coli Serotypes Isolated from Poultry, Wild Animals, and Environment in the Mekong Delta, Vietnam

Abstract: Avian pathogenic Escherichia coli (APEC) is the main causative agent of avian colibacillosis, which is an important systemic disease of profound economic and clinical consequences for the poultry industry worldwide. In this study, 975 E. coli strains were isolated from 2,169 samples collected from cloacal swabs of chickens, in-farm wild animals (ants, geckos, flies, and rats), and environment. The highest proportion of E. coli isolation was obtained from chicken cloacal swabs with 71.05% (95% confidence interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 37 publications
(42 reference statements)
2
8
0
Order By: Relevance
“… Aworh et al (2021) showed that 26.8% of tested samples were positive for E. coli , 42.7% isolated from poultry workers, 32.7% from chickens, and 24.5% from poultry farms’ environments. Consistent with the findings of Nguyen et al (2021) , who found an incidence of 38.11% of E. coli in ecological samples from automatic hatcheries, we found prevalence rates of 31.3, 40, and 100% in the environments of semiautomatic and manual hatcheries, respectively.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“… Aworh et al (2021) showed that 26.8% of tested samples were positive for E. coli , 42.7% isolated from poultry workers, 32.7% from chickens, and 24.5% from poultry farms’ environments. Consistent with the findings of Nguyen et al (2021) , who found an incidence of 38.11% of E. coli in ecological samples from automatic hatcheries, we found prevalence rates of 31.3, 40, and 100% in the environments of semiautomatic and manual hatcheries, respectively.…”
Section: Discussionsupporting
confidence: 91%
“…Serotyping of the E. coli isolates obtained in this inquiry was deemed crucial in order to ascertain the epidemiological status and align with the one health agenda of the relevant organizations. The O:H serotyping was used as the current gold standard grouping for E. coli taxonomy and epidemiology ( Scheutz et al, 2004 ; Nguyen et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the different vectors of APEC such as houseflies, beetles and wild birds are also rodents, and they need to be kept out of poultry houses ( 12 ). Studies of APEC in chickens, wild animals with habitats on farms (including rats), and in the environment in Vietnam revealed complex transmission of E. coli from chickens to wild animals including rodents and to the environment and vice versa ( 47 , 48 ). Although the most important reservoir of verotoxigenic E. coli (VTEC) strains are ruminants, especially cattle, another important reservoir are also rodents, especially rats.…”
Section: Discussionmentioning
confidence: 99%
“…A study carried out in France identified 12 different serogroups, with the most frequently isolated ones being serogroups O2, O8, O25 and O78 [ 13 ]; likewise, a Greek survey mainly identified O78, O2 and O11 [ 14 ]. Studies from different Asian countries highlight a high prevalence of serogroups O78 and O2 [ 15 , 16 ], but also O1 and O18 displayed a relevant prevalence [ 17 ].…”
Section: Introductionmentioning
confidence: 99%